Factors affecting entrepreneurial self-efficacy of engineering students - Kazeem, Akinboye Abayomi; Asimiran, Soaib (Human Resource Management Academic Research Society, 2016)
One of the most significant current discussions in economic development is entrepreneurship. Given government’s commitment to entrepreneurship and innovation, higher institutions of learning are faced with the responsibility of curbing inherent challenges in today’s graduate education. This is of particular concern among engineering students. This study was propelled by the tendency for engineering students to shy away from entrepreneurship as a career choice, particularly when they possess lower entrepreneurial self-efficacy than their fellow business students. A survey of engineering students from a Malaysian public university was conducted using 204 respondents. There were two major data analyses in this study. The relationship between personality traits and entrepreneurial self-efficacy of students were examined. Relationships between family background, as well as entrepreneurship education and entrepreneurial self-efficacy were also explored using Pearson correlation. Results obtained show that the relationship between each personality traits and entrepreneurial self-efficacy are different, emphasizing the relevance of personality traits in enhancing entrepreneurial self-efficacy. Positive correlations were found between family factors and entrepreneurial self-efficacy as well as between entrepreneurship education and entrepreneurial self-efficacy. Furthermore a multiple regression analysis showed that three variables entrepreneurship education, family factor and personality type reliably predicted entrepreneurial self-efficacy among engineering students surveyed. The results of this investigation show that perceived supports from family, competencies gained via entrepreneurship education and personality types affect entrepreneurial self-efficacy of engineering students.